Records of fungal endophytes from canarium ovatum engl. (family burseraceae) leaves - General, Mheljor A.; Guerrero, Jonathan Jaime G. (2017)
The present study investigated the endophytic fungi in pili (Canarium ovatum Engl.), an important tropical tree of Family Burseraceae in the Bicol region. It aimed to identify the species of fungi living as endophytes in the leaves, providing records of such association with the pili tree. It likewise compared the presence of the endophytes in young and mature leaves. Five mature and five young leaves per tree from among five sampled trees were taken as samples. Leaf discs were cut using a 0.64 cm diameter sterilized puncher on two areas within the leaf blade. Sample plant tissues were sterilized using 95% ethanol, 0.4% NaCl, and distilled H2O, at varying time intervals. The plant tissues were transferred to a solidified Potato Dextrose Agar and incubated for seven days at room temperature (26-32 °C). Results yielded the following species: Aspergillus fumigatus Fresen., A. niger Tiegh., A. parasiticus Speare, Geotrichium candidum Link:Fr., Byssochlamys fulva Olliver and G.Sm. and Absidia corymbifera Sacc. &Trotter. It was also noted that endophytes were only present in mature leaves. Research on the potentials for bio-activities of the fungal isolates is recommended.